GENDER-BASED VIOLENCE AND JUSTICE FOR WOMEN SURVIVORS IN RIVERS STATE, NIGERIA, 2015-2025 - Kabee Kpaa; Cynthia Ifeoma Obinwanne (Journal of Social Science, 2026)
Objective: This study examines gender based violence and justice for women survivors in Rivers State, Nigeria from 2015 to 2025. The research aims to identify the key obstacles that prevent women survivors of gender based violence in Rivers State from obtaining effective legal support. Method: A qualitative desk review grounded in feminist legal theory using four research questions was conducted using primary and secondary documents, including court records, media reports, legislation, books, and scholarly journal articles to identify patterns across individual, institutional, and societal levels. Results: Findings reveal that barriers operate at multiple, intersecting levels. At the individual level, stigma, fear of retaliation, economic dependence, and low legal literacy discourage reporting. At the institutional level, justice system delays and poor case handling by law enforcement, pose trust challenges and goes further to retraumatize survivors. At the societal level, patriarchal norms, and cultural practices normalise violence and silence survivors. Novelty: The study concludes that justice for women survivors in Rivers State requires coordinated reforms across the legal, health, and social sectors, alongside community level interventions to shift harmful norms. Key recommendations include establishing specialized gender based violence courts, strengthening survivor centered services, expediting case adjudication, mandating gender sensitivity training for law enforcement and judicial officers, and enforcing the Violence Against Persons Prohibition Act 2015. This study contributes to limited state level data on GBV justice pathways in the Niger Delta. Findings are relevant for policymakers implementing the VAPP Act, NGOs designing survivor support programs, and journalists covering GBV ethically.